HUBUNGAN TINGKAT PENDIDIKAN PADA IBU HAMIL TRIMESTER III DENGAN KUNJUNGAN KE-EMPAT(K4) DI POLINDES MANGUNDIKARAN NGANJUK 2025 - Tri Retnoningsih; Titin Ratnaningsih; Ike Nurrochmawati; Ambar Dwi Retnoningrum; Dewi Indriani (JURNAL SABHANGA, 2026)
Antenatal care is the care or support provided to pregnant women before birth.It is useful for facilitating healthy and positive outcomes for both the mother and her baby byestablishing a trusting relationship with the mother, detecting life-threatening complications,preparing for birth, and providing health education (Ridwan Amiruddin, 2021). Antenatalcare is essential to ensure the natural process of birth proceeds normally and healthily, forboth the mother and the unborn baby